The Students’ Responses of Video Recording and E-Sorogan Learning Methods to Improve Pronunciation - Tiyas Saputri; Mujad Didien Afandi; Anharu Minasalim Mushaf (Bidayatuna, 2022)
Mispronunciation leads to misunderstanding because the inaccuracy in pronouncing words may distort the interpretation of ideas in communication. However, using video recording and e-Sorogan learning methods can be the solution to improve students’ pronunciation, especially the ASD and ADHD student. This study purposes to find out the students' responses to the use of these methods to the 39 elementary students, including a student with ASD and ADHD. This study used descriptive qualitative. The collected data were from the questionnaire survey. Next, the data collected from the questionnaire survey was analyzed descriptive qualitatively through the data in the table and based on empirical data. The results indicated that the students' responses to these methods were positive. It can be proved with the data presented in the table. To conclude, the students agree and even strongly agree with the use of these methods to improve their pronunciation although only a few of them disagree with that. Most of them like these methods because they were appropriate, effective, interesting, useful, and successful to improve their pronunciation. Even, they are able to do self-evaluation and correct the mispronunciation from the video made.